Modelling and numerical simulation of liquid–solid circulating fluidized bed system for protein purification - Pei, Wen; Utikar, Ranjeet; Pareek, Vishnu; Johnson, Stuart; Kale, S.; Lali, A. (Institute of Chemical Engineers (IchemE), Elsevier B.V., 2013)
A novel liquid–solid circulating fluidized bed (LSCFB) was modelled for protein recovery from the feed broth. A typical LSCFB system consists of downer and riser, integrating two different operations simultaneously. A general purpose, extensible, and dynamic model was written based on the tanks-in-series framework. The model allowed adjusting the degree of backmixing in each phase for both columns. The model was validated with previously published data on extraction of bovine serum albumin (BSA) as model protein. Detailed dynamic analysis was performed on the protein recovery operation. The interaction between the riser and downer were captured. Parametric studies on protein recovery in LSCFB system were carried out using the validated model to better understand the system behaviour. Simulation results have shown that both production rate and overall recovery increased with solids circulation rate, superficial liquid velocity in the downer and riser, and feed solution concentration. The model was flexible and could use various forms of ion exchange kinetics and could simulate different hydrodynamic behaviours. It was useful to gain insight into protein recovery processes. The general nature of the model made it useful to study other protein recovery operations for plant and animal proteins. It could also be useful for further multi-objective optimization studies to optimize the LSCFB system.